Job Satisfaction Issue and Its Impact on Teachers’ Performance - Irum, Sumera; Bhatti, Tariq; Mohammad, Noor (Social Science Review Archives, 2025)
The central objective of the research was to examine the relationship between job satisfaction and the performance of teachers in the District of Ghotki in Sindh, Pakistan, in primary schools. This was a descriptive study, and a quantitative research approach was taken. The sample was 3,985 primary school teachers of District Ghotki. The sampling formula that was used to sample 363 teachers is that of Yamane. To get the data, a closed-end questionnaire formed on a five-point Likert scale was created with the assistance of existing literature. The data obtained were then analysed with the help of the Statistical Package for the Social Sciences (SPSS) and Smart-PLS software. Data analysis was performed with the help of Descriptive statistics, reliability analysis, and Partial Least Squares Structural Equation Modelling (PLS-SEM). The overall results of the research indicated that job satisfaction affects the performance of teachers positively. The organizational issues, including pay, promotion prospects and head teacher behaviour, were also identified to play a significant role in the performance of teachers. The research has determined that the motivation and performance of teachers may be increased through the improvement of organizational conditions. It is suggested that the educational authorities need to enhance the pay scale, offer transparent promotion reports, and foster good leadership practices to enhance teacher conduct and school results.